Influences Des Modes D’accès A La Terre Sur La Production Agricole Dans Les Communes De Dassa-Zoumé Et De Glazouè Au Centre Du Bènin - Gislain, Kadjegbin Toundé Roméo; Ibouraima, Yabi; Théodore, Adjakpa T.; Parfaite, Kotchare; Grégoire, Sewade Sokegbe; Sègbè, Houssou Christophe (European Scientific Journal, ESJ, 2018)
The land plays an important role in the social and economic life of the populations of all of the world in general and in the rural world in particular in such a way that it constitutes the essential support of every agricultural activity. The purpose of this article is to study the influence of the access to land on the agricultural production in the communes of Dassa-Zoumé and Glazoué. From a sample of 279 farm households, the study of the influence of land access on the agricultural production in the communes of Dassa-Zoumé and Glazoué was made using the questionnaire sent to farmers and CARDER/Zou authorities. In order to collect reliable information, a presurvey was carried out at first, followed by an individual interview, a focus group and a MARP ( Active Participatory Research Method). Similarly, the SWOT analyses model was used and the Ruthenberg coefficient was calculated to better appreciate the cropping system used in both communities. At the end of the analyses, we can notice that in the communes of DassaZoumé and Glazoué, inheritance remains the main modes of access to land with 82,9%, followed by ‘’donation’’with5,1%, then the borrowingwith4,3% and the collective appropriation(2,6%), renting(1,7%), sharecropping(1,7%) and the purchase(1,7%). OF these different modes of access, the inheritance is the most privileged while renting, sharecropping and buying constitute binding modes. These different modes of access determine the different uses that can be made of rural land and constitute either a constraint or an asset for agricultural production.